2018
DOI: 10.4067/s0718-95162018005002002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of natural fertilizer extracted from expired dairy products as a soil amendment

Abstract: Dairy products contain high level of minerals and organic materials. The disposal of these materials is a source of environmental pollution and recourses loss. Recycling of expired dairy products is the ideal practical solution for an integrated ecosystem. Thus, a greenhouse trails were carried out to investigate the effectiveness of natural fertilizer extracted from expired dairy products. Expired dairy products powder (EDPP) was applied to wheat (Triticum aestivum vulgar) plants grown on pots filled with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 15 publications
(23 reference statements)
6
20
0
Order By: Relevance
“…These results regarding the improvement in soil quality as a result of organic fertilization are consistent with those obtained from the studies of Alharbi et al [4] and Rekaby et al [43]. Organic fertilizers increase the organic matter content and nutrient availability in soil [43,44]. Moreover, organic fertilizers play im-…”
Section: Discussionsupporting
confidence: 90%
“…These results regarding the improvement in soil quality as a result of organic fertilization are consistent with those obtained from the studies of Alharbi et al [4] and Rekaby et al [43]. Organic fertilizers increase the organic matter content and nutrient availability in soil [43,44]. Moreover, organic fertilizers play im-…”
Section: Discussionsupporting
confidence: 90%
“…Biochar as an organic amendment improves the level of soil organic matter, which helps to maintain water and nutrient retention, contributing to the sustainability of the cropping systems and higher nutrient use efficiency [34]. Moreover, biochar could store nutrients and be used as a slow-release fertilizer [50,51] thanks to its specific properties such as pore structure and functional groups [50,51,56,[66][67][68]. Some inorganic forms of N can be adsorbed to BC and minimize the emission of ammonia and nitrate leaching from soil [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, very few studies are found on the extraction of protein from expired sources. Recycling of expired products can be a model for an integrated ecosystem (Eissa et al., 2018; Tham et al., 2019). Expired dairy products were essentially considered as an organic fertilizer in comparison to inorganic fertilizer to grow wheat ( Triticum aestivum vulgar ) (Eissa et al., 2018).…”
Section: Food Waste Protein Sources and Usesmentioning
confidence: 99%
“…Recycling of expired products can be a model for an integrated ecosystem (Eissa et al., 2018; Tham et al., 2019). Expired dairy products were essentially considered as an organic fertilizer in comparison to inorganic fertilizer to grow wheat ( Triticum aestivum vulgar ) (Eissa et al., 2018). The results of the study concluded a significant increase in total chlorophyll by 22% and nitrogen (N), phosphorus (P), and potassium (K) uptake by 54%, 67%, and 14% when expired dairy powder was used in place of inorganic fertilizer.…”
Section: Food Waste Protein Sources and Usesmentioning
confidence: 99%